(untitled) (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
The evolution of investment projects has accelerated in both developing and developed economies over the past two decades. In Uzbekistan, foreign direct investment (FDI) has played a key role in boosting growth, productivity, and technological advancement. This study examines the impact of FDI inflows on GDP growth and investment project efficiency from 2000 to 2024. It also highlights the role of digital technologies—such as blockchain, artificial intelligence, and big data—in enhancing transparency, efficiency, and investor confidence. Recommendations include improving investment protection, expanding PPP frameworks, and directing FDI toward manufacturing and high-value services.